Microfluidic platform for next-generation sequencing library preparation with low-input samples - Murphy, Travis W. (Anal Chem, 2020)
Advances in Next Generation Sequencing (NGS) have made available a wealth of information that had previously been inaccessible to researchers and clinicians. NGS has been applied to understand genomic, transcriptomic, and epigenomic changes and gained traction as a significant tool capable of accelerating diagnosis, prognosis, and biomarker discovery. However, these NGS assays have yet to be practical methods for patient stratification or diagnosis because of the gap between the tiny quantities of biomaterials provided by a clinical sample and the large DNA input required by most of these assays. Current library preparation methodologies typically require large input amounts of DNA and a long and complicated manual process. Here, we present a microfluidic droplet-based system for NGS library preparation, capable of reducing the number of pipetting steps significantly, reducing reagent consumption by 10x, automating much of the process, while supporting extremely low DNA input requirement (10 pg per library). This semiautomated technology will allow for low-input preparations of 8 libraries simultaneously while reducing batch-to-batch variation and operator hands-on time.